Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 194548 by horsebrand11 last updated on 09/Jul/23

Commented by horsebrand11 last updated on 09/Jul/23

 ⋗^()

Answered by deleteduser1 last updated on 09/Jul/23

((y−1)/(x−1))=((1−0)/(1−0))⇒y=x(equation of line)  ∫_0 ^1 xdx=(x^2 /2)∣_0 ^1 =(1/2)  x(x−2)^2 =x(x^2 −4x+4)=x^3 −4x^2 +4x  ⇒∫_1 ^2 (x^3 −4x^2 +4x)dx=(x^4 /4)−((4x^3 )/3)+2x^2 ∣_1 ^2 =(5/(12))  ⇒R_2 =(5/(12))+(1/2)=((11)/(12))  Similarly,we get ∫_0 ^2 x(x−2)^2 =(4/3)⇒R_1 =(4/3)−((11)/(12))=(5/(12))

y1x1=1010y=x(equationofline)01xdx=x2201=12x(x2)2=x(x24x+4)=x34x2+4x12(x34x2+4x)dx=x444x33+2x212=512R2=512+12=1112Similarly,weget02x(x2)2=43R1=431112=512

Answered by MM42 last updated on 09/Jul/23

  R_1 =∫_0 ^1 x(x−2)^2 dx−(1/2)=(5/(12))  R_2 =∫_0 ^2 x(x−2)^2 dx−R_1 =((11)/(12))

R1=01x(x2)2dx12=512R2=02x(x2)2dxR1=1112

Terms of Service

Privacy Policy

Contact: info@tinkutara.com